SYNTHESIS, STRUCTURAL CHARACTERIZATION AND “IN VITRO” EVALUATION OF BIOACTIVITY OF SILVER CONTAINING BIOACTIVE GLASSES - POPESCU, R. A.; MAGYARI, K.; PAPUC, I.; BAIA, L. (Studia Universitatis Babeș-Bolyai Physica, 2015)
Five silver doped SiO2–CaO–P2O5 based bioactive glasses were synthesized and structurally characterized in order to find the optimal concentration that can be further used in scaffold fabrication for bone tissue engineering. Initially, the recorded XRD patterns confirmed the existence of a preponderantly amorphous structure for all samples, though the presence of some crystallization centres associated with tricalcium phosphate phase was also revealed. The UV-vis spectra evidenced signal originated from the surface plasmon resonances of the silver nanoparticles. The signature of both types of isolated and cluster silver nanoparticles were signalized, the amount of the silver aggregates was found to progressively increase starting with 0.5 mol% Ag2O. Bioactivity assessment was also performed for the obtained samples, and it was determined a good response to all compositions. However, for the sample with 0.5 mol% Ag2O the content of the self-assembled hydroxyapatite phases was more noticeable and also was taken into consideration the absence of a high signal from AgCl. This can be considered the optimum concentration of silver, from the obtained samples range, that can be further used for scaffold preparation.